On Some w−Interpolative Contractions of Suzuki-Type Mappings in Quasi-Partial b-Metric Space. (13th April 2022) - Gautam, Pragati; Kumar, Santosh; Verma, Swapnil; Gulati, Soumya
Abstract : In this paper, our focus is to acquaint with the Suzuki-type mappings to establish some fixed point results using the new w-interpolative approach. We present some results for interpolative contraction operators via the w-admissible maps which satisfy the Kannan, Ćirić–Reich–Rus, and Hardy–Rogers contractions in quasi-partial b-metric space. Further, the outcomes so obtained are affirmed with relevant examples.